Strongyloides stercoralis Infection in Solid Organ Transplant Patients Is Associated With Eosinophil Activation and Intestinal Inflammation: A Cross-sectional Study. (10th March 2020) - Clark, Eva; Pritchard, Haley; Hemmige, Vagish; Restrepo, Alejandro; Bautista, Karla; Damania, Ashish; Ricciardi, Alessandra; Nutman, Thomas B; Mejia, Rojelio
Abstract: Background: Strongyloidiasis can cause devastating morbidity and death in immunosuppressed patients. Identification of reliable biomarkers for strongyloidiasis in immunosuppressed patients is critical for the prevention of severe disease. Methods: In this cross-sectional study of solid organ transplant (SOT) candidates and recipients, we quantified Strongyloides -specific IgG to the recombinant NIE-Strongyloides antigen and/or to a soluble extract of S. stercoralis somatic antigens ("crude antigen") using enzyme-linked immunosorbent assays (ELISAs). We also measured peripheral eosinophilia, 4 different eosinophil granule proteins, and intestinal fatty acid–binding protein (IFABP). Results: We evaluated serum biomarkers in 149 individuals; 77 (52%) pre-SOT and 72 (48%) post-SOT. Four percent (6/149) tested positive by NIE ELISA and 9.6% (11/114) by crude antigen ELISA (overall seropositivity of 9.4% [14/149]). Seropositive patients had higher absolute eosinophil counts (AECs) than seronegative patients ( P = .004). AEC was positively correlated to the levels of eosinophil granule proteins eosinophil cationic protein (ECP) and eosinophil peroxidase (EPO) ( P < .05), while IFABP was positively related to the 2 other eosinophil granule proteins (major basic protein [MBP] and eosinophil-derived neurotoxin [EDN]; Spearman's r = 0.3090 and 0.3778, respectively; P < .05; multivariate analyses slopes = 0.70 and 2.83, respectively). Conclusions: This study suggests that, in SOT patients, strongyloidiasis triggers both eosinophilia and eosinophil activation, the latter being associated with intestinal inflammation. These data provide insight into the pathogenesis of S. stercoralis infection in the immunocompromised population at high risk of severe strongyloidiasis syndromes. Abstract : It is critical to diagnose strongyloidiasis prior to solid-organ transplantation (SOT) to prevent severe strongyloidiasis syndromes. This cross-sectional study evaluated serum biomarkers for eosinophil activation and intestinal inflammation to provide insight into the pathogenesis of strongyloidiasis in SOT patients.